Market leader : - Mascull, Bill (Pearson Education, 2007)
This four-level series ¿ with a brand-new course for beginning students ¿ develops language skills, expands vocabulary, and increases students¿ grasp of business concepts with: Coverage of relevant business topics, including ethics, globalization, branding, leadership, and innovation. Material drawn from a wide range of respected business sources and supported by language and skills exercises and useful case studies